Targeting clinical epigenetic reprogramming for chemoprevention of metabolic and viral hepatocellular carcinoma. Issue 1 (26th March 2020) - Jühling, Frank; Hamdane, Nourdine; Crouchet, Emilie; Li, Shen; El Saghire, Houssein; Mukherji, Atish; Fujiwara, Naoto; Oudot, Marine A; Thumann, Christine; Saviano, Antonio; Roca Suarez, Armando Andres; Goto, Kaku; et al.
Abstract : Objective: Hepatocellular carcinoma (HCC) is the fastest-growing cause of cancer-related mortality with chronic viral hepatitis and non-alcoholic steatohepatitis (NASH) as major aetiologies. Treatment options for HCC are unsatisfactory and chemopreventive approaches are absent. Chronic hepatitis C (CHC) results in epigenetic alterations driving HCC risk and persisting following cure. Here, we aimed to investigate epigenetic modifications as targets for liver cancer chemoprevention. Design: Liver tissues from patients with NASH and CHC were analysed by ChIP-Seq (H3K27ac) and RNA-Seq. The liver disease-specific epigenetic and transcriptional reprogramming in patients was modelled in a liver cell culture system. Perturbation studies combined with a targeted small molecule screen followed by i n vivo and ex vivo validation were used to identify chromatin modifiers and readers for HCC chemoprevention. Results: In patients, CHC and NASH share similar epigenetic and transcriptomic modifications driving cancer risk. Using a cell-based system modelling epigenetic modifications in patients, we identified chromatin readers as targets to revert liver gene transcription driving clinical HCC risk. Proof-of-concept studies in a NASH-HCC mouse model showed that the pharmacological inhibition of chromatin reader bromodomain 4 inhibited liver disease progression and hepatocarcinogenesis by restoring transcriptional reprogramming of the genes that were epigenetically altered in patients. Conclusion: Our results unravel the functional relevance of metabolic and virus-induced epigenetic alterations for pathogenesis of HCC development and identify chromatin readers as targets for chemoprevention in patients with chronic liver diseases.